Human Excretion of Polybrominated Diphenyl Ether Flame Retardants: Blood, Urine, and Sweat Study. - Genuis, Shelagh K.; Birkholz, Detlef; Genuis, Stephen J. (BioMed Research International, 2017)
Commonly used as flame retardants, polybrominated diphenyl ethers (PBDEs) are routinely detected in the environment, animals, and humans. Although these persistent organic pollutants are increasingly recognized as having serious health implications, particularly for children, this is the first study, to our knowledge, to investigate an intervention for human elimination of bioaccumulated PBDEs. Objectives. To determine the efficacy of blood, urine, and perspiration as PBDE biomonitoring mediums; assess excretion of five common PBDE congeners (28, 47, 99, 100, and 153) in urine and perspiration; and explore the potential of induced sweating for decreasing bioaccumulated PBDEs. Results. PBDE congeners were not found in urine samples; findings focus on blood and perspiration. 80% of participants tested positive in one or more body fluids for PBDE 28, 100% for PBDE 47, 95% for PBDE 99, and 90% for PBDE 100 and PBDE 153. Induced perspiration facilitated excretion of the five congeners, with different rates of excretion for different congeners. Conclusion. Blood testing provides only a partial understanding of human PBDE bioaccumulation; testing of both blood and perspiration provides a better understanding. This study provides important baseline evidence for regular induced perspiration as a potential means for therapeutic PBDE elimination. Fetotoxic and reproductive effects of PBDE exposure highlight the importance of further detoxification research.